Qona'ah on Badiuzzaman Said Nursi Perspective: Analysis of Happy Model in Dimensions of Gratitude - Jarman Arroisi; Nurmala Indah (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2023)
In this modern era, many people are looking for happiness that is only based on material things without paying attention to peace of mind. This can be seen very clearly in the lives of Westerners who only make material life a source of happiness and satisfaction. So that the happiness that is obtained is not eternal and eternal, because gratitude is not accompanied by them being able to enjoy all aspects of life.This research was conducted to determine Badiuzzaman Said Nursi's qana'ah perspective based on the Dimensions of Gratitude. First, the analysis usess qualitative methods, and data collection is carried out using a literature search. After that, the data that has been collected is described descriptively to explain each of the related discussion suburbs. Then the results of this study show that to get to the attitude of qona'ah, it is necessary to apply the perspective of the business, willing, resignation, gratitude, prayer, and sharing. According to Said Nursi, the highest level of qana'ah is to become ahsana taqwim by passing the four foundations of ubudiyah and mahbubiyah, including absolute weakness (al-Ajz), Absolute Factory (al-Faqr), absolute longing (asy-Syafaqah) and absolute gratitude (at-Tafakkur).